Understanding Salmonella enterica serovar Dublin as a cause of abortion in cattle - Franklin, Jemma May (2023)
Salmonella enterica serovar Dublin (S. Dublin) is a host-adapted non-typhoidal Salmonella serovar associated with disease predominantly in cattle as well as a variety of other species including humans. S. Dublin is one of the most common infectious causes of bovine abortion in the UK and is the most commonly isolated Salmonella serovar from cattle. S. Dublin can persist in the environment and reside in sub-clinically infected animals, making it extremely difficult to eradicate on farm. Infection in cattle is acquired via the faecal oral route, and the bacterium can be shed in faeces, urine and milk. As a zoonotic disease, S. Dublin also poses a risk to human health and food security, with many cases in humans being found to be associated with consumption of contaminated dairy and beef products. Additionally, an abortion in a dairy herd in the UK is estimated to cost upwards of £630 (Cabell, 2007).